PERSONAL BRANDING MANAGEMENT OF RIFAT SUNGKAR THROUGH BRAND SOCIAL RESPONSIBILITY STRATEGY IN SOCIAL MEDIA - Ismaya Dian Putri Hendarsih; Bambang Sukma (Jurnal Scientia, 2023)
Currently, social media has become an alternative media to promote something in the market, including introducing oneself to the general public or commonly known as personal branding. Rifat Sungkar , a national racer also does this with his social media. The writer conducting research on social media Rifat Sungkar to investigate and analyze the Brand Social Responsibility (BSR) strategy he did in personal branding, identify factors that play an important role from the BSR aspect in personal branding development and analyze the role of social media in supporting personal success. branding of a Rifat. The author conducted research with a descriptive qualitative approach using the case study method. This study uses three main aspects in personal branding, namely distinctive, relevant and consistent characteristics and uses eight aspects in the BSR, namely charitable, linkable, responsible, investible, sustainable, communicable, collaborative and inspirational. The results of this study indicate that Rifat Sungkar has succeeded in implementing personal branding with the BSR strategy which produces content that is beneficial to the general public through his social media.